Aproximações entre psicanálise e escrita de rua - Nunes, Rafael José Triches (2018)
It is arduous to determine the reasons that led to the conception of psychoanalysis, but it is possible to affirm that since the conception of the concept of the unconscious, psychoanalysis shows great affinity with the world of Art. The object of this study is street writing, an urban art form that includes several styles such as graffiti and street art, initially seen as vandalism, it undergoes a process of social acceptance in which the inscriptions are authorized or even commissioned. In the course developed in this dissertation, it is possible to problematize the relationship between these two areas of knowledge by taking artistic creation as a product of sublimation, one of the destinies of the drives and, therefore, a witness to the way the unconscious operates. Freud's writings, such as The Interpretation of Dreams and Malaise in Culture, were mainly consulted and also authors outside the psychoanalytic field, such as Rancière. It is worth emphasizing that the concepts of desire, drive and sublimation are placed as the central point of the unconscious creative act. Finally, from a critical analysis of street writing, it is possible to reflect on the relevance of urban inscriptions for the formation of subjectivity, as well as for the formal and informal means of education, especially emancipatory practices.